Review of a mock research protocol in functional neuroimaging by Canadian research ethics boards - de Champlain, J (BMJ Group, 2006)
OBJECTIVE: To examine how research ethics boards (REBs) review research projects in emerging disciplines such as functional neuroimaging. DESIGN: To compare the criteria applied and the decisions reached by REBs that reviewed the same mock research protocol in functional neuroimaging. PARTICIPANTS: 44 Canadian biomedical REBs, mostly working in public university or hospital settings. MAIN MEASUREMENTS: The mock research protocol “The Neurobiology of Social Behavior” included several ethical issues operating at all three levels: personal, institutional and social. Data consisting of responses to closed questions were analysed quantitatively. Qualitative analysis of open‐question responses used mixed classification. RESULTS: Similar criteria were used by most participating REBs. Yet the project was unconditionally approved by 3 REBs, approved conditionally by 10 and rejected by 30. CONCLUSIONS: The results point to the difficulty for REBs of reviewing all kinds of research projects, regardless of field, by relying on international and national norms framed in general terms and a possible variation between REBs in the interpretation of their mandate for the protection of research subjects.